Effect of precursor mass on product phase composition in plasma dynamic synthesis of tungsten carbide; Journal of Physics: Conference Series; Vol. 830 : Energy Fluxes and Radiation Effects 2016 - Shatrova K. N.; Sivkov A. A. Aleksandr Anatolyevich; Shanenkov I. I. Ivan Igorevich; Saigash A. S. Anastasiya Sergeevna (Modification of materials with particle beams and plasma flows, 2017)
Title screen